THE USE OF GENRE-BASED APPROACH TO IMPROVE WRITING SKILL IN NARRATIVE TEXT AT THE ELEVENTH GRADE STUDENTS OF SMA ETHIKA PALEMBANG - Haryanti, Haryanti; Sari, Farnia (English Community Journal, 2019)
Objective of this research was to find out significant difference of reading achievement between students The objective of this study was to find out whether or not there was a significant improvement in students' skill in writing narrative texts after they were taught by using Genre-Based Approach. The method of this study was experimental design. The experimental group received a genre-based approach while the control group received the conventional method. The population was the eleventh-grade students of SMA Ethika Palembang. The sample was 60 students which was selected by cluster random technique . The data collection was a writing test. The data were analyzed by using paired sample t-test and independent sample t-test. It indicated that there was a significant difference in writing skill between the students who were taught using GBA and those who were not.  Based on the result of data, it was interpreted that all aspects of writing are increased after taught by using GBA Approach. The best-achieved writing aspect was style and quality expression. It assumed the use of words: phrases, sentences, and paragraphs in expressing the ideas were clear and effective in writing style. Further, the study provided evidence for the effectiveness of using the genre-based approach in improving the students' writing skill in narrative text.